2010
DOI: 10.1186/1471-2334-10-73
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the 23-valent polysaccharide pneumococcal vaccine against invasive pneumococcal disease in people 60 years or older

Abstract: BackgroundThe 23-valent polysaccharide pneumococcal vaccine (PPV) is currently recommended in elderly and high-risk adults. However, its efficacy in preventing pneumococcal infections remains controversial. This study assessed the clinical effectiveness of vaccination against invasive pneumococcal disease (IPD) among people over 60 years.MethodsPopulation-based case-control study that included 88 case patients over 60 years-old with a laboratory-confirmed IPD (bacteraemic pneumonia, meningitis or sepsis) and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
1
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(30 citation statements)
references
References 35 publications
1
26
1
2
Order By: Relevance
“…Meta-analyses of five randomized clinical trials have shown that PPV23 is 68% (95% CI 53-78) effective against IPD among immunocompetent older adults. 49 In our analyses, the values for vaccine effectiveness against were based on multiple observational studies which had the advantage of being conducted in large unselected natural populations 11,37,[50][51][52][53][54][55] (Table 3). One of these recent studies, conducted in Scotland in persons aged ≥65 years, demonstrated a protective effect of PPV23 against IPD of 61.7% (95% CI, 45.1-73.2).…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…Meta-analyses of five randomized clinical trials have shown that PPV23 is 68% (95% CI 53-78) effective against IPD among immunocompetent older adults. 49 In our analyses, the values for vaccine effectiveness against were based on multiple observational studies which had the advantage of being conducted in large unselected natural populations 11,37,[50][51][52][53][54][55] (Table 3). One of these recent studies, conducted in Scotland in persons aged ≥65 years, demonstrated a protective effect of PPV23 against IPD of 61.7% (95% CI, 45.1-73.2).…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…Several studies have examined the responses to PCV or PPSV vaccination in at-risk adults [13][14][15][16][17][18][19]; to date, no studies specifically examined responses after PCV13 vaccination in at-risk adults. Therefore, in this analysis, we evaluated data from 3 previous studies in immunocompetent PPSV23-naive and PPSV23-preimmunized subjects ≥50 years of age that included a considerable percentage of subjects with stable chronic underlying conditions known to put these subjects at increased risk for pneumococcal disease.…”
Section: Discussionmentioning
confidence: 99%
“…40,41 Further, it is possible that some patients did not report vaccinations they received outside of the Veterans Affairs healthcare system to their Veterans Affairs provider; however, this potential misclassification is likely to be low, as the vaccination rate in the overall Veterans Affairs cohort with pneumococcal infection was similar to a community population with serious pneumococcal infections (33% vs 38%). 42 Extrapolation of these results to the general population is also limited, as the population primarily consisted of older white men.…”
Section: Limitationsmentioning
confidence: 99%